Deaths in Custody Reporting Program: State Prisons, 2001 - 2013 ([Verlag nicht ermittelbar], 2016)
The Deaths in Custody Reporting Program (DCRP) is an annual data collection conducted by the Bureau of Justice Statistics (BJS). The DCRP began in 2000 under the Death in Custody Reporting Act of 2000 (P.L. 106-297). It is the only national statistical collection that obtains detailed information about deaths in adult correctional facilities. The DCRP collects data on persons dying in state prisons, local jails and in the process of arrest. Each collection is a separate subcollection, but each is under the umbrella of the DCRP collection. This deals with the prison subcollection, which has a prison death file. The prison portion of the Deaths in Custody Reporting Program began in 2001 after the passage of the Deaths in Custody Reporting Act of 2000 in October of 2000. The prison component of the DCRP collects data on inmate deaths occurring in the 50 state departments of corrections while inmates are in the physical custody of prison officials.